Phenomenological Investigation on the Academic Experience of International Palestinian Student Studying at Universitas Muhammadiyah Surakarta - Oktaviana, Choiril Berlian; , Fitri Kurniawan M.Ed.Res (2017)
This study is aimed to explore the academic experience of international Palestinian student studying at Universitas Muhammadiyah Surakarta and the efforts done by the participant in facing the academic problems. In achieving the objectives, the researcher used hermeneutic phenomenological study as an approach to collect and analyze the data. The research recruited a Palestinian international student studying at Universitas Muhammadiyah Surakarta to participate in the research. The technique for collecting data is repeated semi-structured in depth-interview as data collection. The result of the analysis shows that the participant perceives two aspects of academic experience covered physical and non-physical aspects when studying at Universitas Muhammadiyah Surakarta. The physical aspects included the facility covered the boarding house issue, the availability of descent laboratory tools, insufficient English book collection in library. The non-physical aspect more stressful on the teaching activity, culture, attitude of Indonesian people and accommodation. There are three active efforts done by the participant in facing the academic problems, begins from learning Bahasa Indonesia, keep coming to go to campus and borrow Indonesian friend's motorcycle to go to places far from campus. However, there is a limited capacity of the participant to do beyond the situation related to the facilities and boarding house provided by university.